RECUPERACIÓN DE PERCLORETILENO EN INDUCALSA - H., Brito; D., Borja; N., Moreno; M., Parada; P., Robalino; M., Mendoza; E., Andrade (European Scientific Journal, ESJ, 2015)
A recovery system for perchlorine ethylene from hazardous liquid waste (Ministry Agreement 026 MAE) which stems from shoe making polyurethane sole washing has been designed (Brito H. / Rodríguez B., 2014). Such waste is directly disposed into the environment, causing losses in flora and fauna (GUARIN, O. / RUEDA, G. / PEREZ, H. 2010). Besides contributing with environmental liabilities, the recovered perchlorine ethylene complies the requirements of the DIRSA safety card, because of what it is reutilized in the manufacture process, which contributes to the decrease of production costs and the conservation of the ecosystem. This hazardous waste should be delivered to an environmental manager before paying for its transportation and final disposal (90 USD per kg of waste). For this reason, INDUCALSA along with ESPOCH researchers carried out a scaling of the recovery system by working with 20 samples of perchlorine ethylene – silicone during a lapse of four weeks. An initial characterization was followed by in – lab recovery to measure the variables (temperature, time, input and output flow) with whom the process was scaled for 45,73 Kg/h of waste. The pH, density, viscosity and IR spectrum of the obtained product were analyzed. They showed the purity of the solvent (Disolventes Reunidas, S.A., 2003), which is acceptable because of its high economic value in the market as well as the contribution to the change of the productive matrix in Ecuador (SENPLADES, 2012).